Ultrasound with use of Doppler for assess the effectiveness of chemoradiotherapy for cervical cancer - T. E. Gorbushina; O. V. Astafieva (Кубанский научный медицинский вестник, 2015)
The analysis of ultrasound studies of 98 patients with cervical cancer II-III stage before treatment and after a course of chemo-radiotherapy (CRT). Found changes in cervix in gray-scale. The use of Doppler in the study of intratumoral blood flow possible to determine increasing index resistance (IR) in 47 women with good outcome treatment of the disease (criterion Wilcoxon, p < 0.05) after a course of CRT. Remained abnormal blood flow (IR = 0.2-0.46) in 51 women with bad outcome treatment of the disease. To evaluate the effectiveness of the CRT of cervical cancer should be used Doppler.